Investigating business' contribution to climate change governance in areas of limited statehood: the case of South Africa and Kenya - Kapfudzaruwa, Farai (Graduate School of Business (GSB), 2019)
Climate change and the related social and economic challenges present society with problems at multiple levels. There is a diverse range of actors who are contributing to climate change governance, including those who are going to be affected by the impacts. In areas of limited statehood were states have varying degrees of deficits in their abilities to steer effective climate change mitigation and adaptation, private actors such as business organisations are expected to step in. This research set to investigate how and why companies in South Africa and Kenya contribute to climate change governance. South Africa and Kenya are selected because they represent areas which have varying levels of limited statehood. The results from the content analysis and the case studies reveal that companies’ climate change governance contributions can be characterised into four configurations: laggards, emergent planners, efficiency drivers and visionaries. The laggards display very limited responses and if anything adopt cosmetic initiatives. The majority of Kenyan and South African firms are in this cluster. Emergent planners are in the early stages of implementing self-regulatory initiatives mostly at the firm level. The efficiency drivers which consist of mostly energy intensive companies engage in co-regulation which involves partnering with the state to set and implement rules in energy efficiency accords in both countries. The firms, in turn, self-regulate themselves by internally implementing the energy efficiency accord guidelines. The final configurations, the visionaries, make more comprehensive mitigation and adaptation governance contributions focusing on collective self-regulation and adopting the role of the “inspector” along their supply chain. On the basis of these empirical findings, the research identifies different ways in which the institutional, organisational and issue specific drivers interact to explain the variations in firms’ governance contributions between countries, sectors and different companies. First, corporate climate change governance contributions vary between South Africa and Kenya as a result of the countries’ different levels of statehood. South African firms are more responsive to climate change than Kenyan companies because they are more exposed to the shadow of hierarchy. Statehood is a significant factor in the context of possible alternative explanations. Second, the climate change governance contributions vary between sectors due to the combined effect of the shadow of anarchy and the task complexity associated with securing energy or water supply among “high salience” sectors. Furthermore, carbon intensive sectors have strong associations which enable them to address collective problems linked to climate change. Lastly, there are significant levels of variance in the governance contributions between the different types of companies, that is, between large, multinational companies and smaller, domestic firms. The large firms engage in more comprehensive mitigation and adaptation efforts due to organisational factors which include “asset specificity” and organisational resources.